ANALISIS FRAUD DIAMOND UNTUK MENDETEKSI TERJADINYA FINANCIAL STATEMENT FRAUD DI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2015) - Lutfiana Oktarigusta (Jurnal Manajemen Dayasaing, 2017)
This study aimed to analyze the influence of the four elements in Fraud Diamond to detect possible Financial Statement Fraud. Fraud diamond consists of pressure element, opportunity, rationalization and capability. The fourth element is to be divided into seven variables: financial stability by proxy assets changes (ACHANGE), financial presure by proxy Return on Assets (ROA), external presure by proxy Leverage (LEV), the nature of  industry by proxy Receivable (REC), effectiveness supervision by proxy the number of independent directors (BDOUT), rationalization of the proxy Total acrual to Total Assets (TATA), and the capability to proxy the change of directors (DCHANGE) to detect possible financial statements fraud as measured by M Score models. This study use  purposive sampling to select a representative sample. This reseach use periode 2011-2015 as an abservation periode. The collected data is analized using logistic regresion. This study show that there are two (2) variables: the effectiveness of supervision by the proxy of the number of independent commissioners (BDOUT) and rationalization by proxy Total acrual to Total Assets (TATA) that significantly influence the possibility of financial statements fraud. While five other variable whitch consists of financial stability, financial presure, external presure, nature of industry, and the capability do not have significantin influent on financial statements fraud.